A new journal for a new era in neonatology - Robert L Schelonka (Dove Medical Press, 2011)
Robert L SchelonkaOregon Health and Sciences University, Portland, OR, USAThe specialty of neonatal medicine is young, only about 50 years old by most accounts. Despite its youth, the magnitude and pace of discovery in our field has been dizzying. Little seems more illustrative of this than considering a 1-kg infant who was born in 1960 had a mortality risk of 95%; however, by the year 2000, a 1-kg infant had a 95% chance of surviving.1 This remarkable progress has been fueled by the fact that clinicians and investigators alike have embraced discovery in our field. I recently searched PubMed under the broad topic of “neonate” and received over half a million hits; the search term “preterm infant” yielded 34,000 hits, and the terms “infection in neonates”, a particular research interest of mine, gave 50,000 hits. Given this degree of scholarly activity in our field, one might conclude we have already answered the important questions we face when caring for newborn infants.